Office‐Based Surgical Procedures in Rhinology. (2nd September 2014) - Lee, Jivianne T.; Han, Joseph; Hwang, Peter H.; Stringer, Scott P.
Abstract : Program Description: With continual advances in endoscopic instrumentation and technology, a burgeoning number of rhinologic procedures can now be effectively performed in the office environment. Such interventions have provided therapeutic alternatives in the management of primary and recalcitrant sinonasal disease. The purpose of this miniseminar is to describe the principles and techniques involved in successful implementation of rhinologic surgery in the clinic setting. Both fundamental (turbinate surgery, polypectomy) and advanced sinus procedures (frontal sinusotomy, revision surgery) will be discussed. Appropriate setup, anesthesia, and patient selection will be described. This miniseminar will be conducted by academic leading rhinologists using a multimedia, interactive, case‐based format. Educational Objectives: (1) Discuss current office‐based, rhinologic surgical procedures and their role in the management of sinonasal disease. (2) Describe appropriate patient selection, preparation, and optimal anesthetic and surgical techniques for rhinologic clinic procedures. (3) Assess recent technologic innovations and understand their proper application in rhinologic office‐based surgical procedures.